ITEM ANALYSIS OF MULTIPLE-CHOICE QUESTIONS IN AN UNDERGRADUATE SURGERY COURSE-AN ASSESSMENT OF AN ASSESSMENT TOOL - Al Sulaim , Lamees Sulaiman; Salati, Sajad Ahmad (Sanamed, 2024)
Introduction: In the field of medical education, multiple-choice questions (MCQs) represent the most commonly utilized method of assessment. It is necessary to analyze the assessment results through item analysis to ensure the quality is appropriate. This study evaluated the quality of the MCQs utilized for summative evaluation of the students in the General Surgery Course conducted in the year 2023-24, at the College of Medicine (Unaizah), Qassim University, Saudi Arabia.Methods: Using a number of established parameters for item analysis, the study evaluated the multiple-choice questions for difficulty, discrimination power, and quality of distractors.Results: The quality of the questions varied. The means of the facility index, discrimination index, discriminative efficiency, and distractor efficiency were, in order, 76.31%, 0.28, -0.7743, and 32%.Conclusion: Item analysis is a crucial technique for evaluating the quality of MCQs. There were multiple defects in the MCQs used in summative assessments, revealing the scope for further improvement in future courses. It is important to plan faculty development events often to impart knowledge and skills related to creating MCQs that are valid, reliable, and of high quality.
Keywords: Assessment; Item analysis; Multiple-choice questions; Facility index; Discriminative index; Distractor efficiency; Non-functional distractor; Distractor analysis.